2006
DOI: 10.1074/jbc.m604607200
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 GTPase Regulates Cell Genomic Stability and Senescence

Abstract: The Rho family small GTPase Rac1 has been shown to play multiple roles in cell regulation, including actin cytoskeleton organization, transcriptional activation, microtubule dynamics, and endocytosis. Here, we report a novel role of Rac1 in regulating genomic stability and cell senescence. We observed in primary mouse embryonic fibroblasts that deletion of rac1 by gene targeting, as well as expression of the constitutively active Rac1 mutant L61Rac1, led to decreased cell growth that was associated with altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 51 publications
(91 reference statements)
3
39
0
3
Order By: Relevance
“…These oncogenes are able to transform cells, but only in collaboration with other oncogenes such as MYC (31,32). Similar results have been described for ectopic expression of other components of the RAS pathway, such as RAC1 and RAF (33,34), as well as other oncogenes, including E2F and STAT5A (35,36). Although, in most studies, these experiments were conducted in primary fibroblasts or other primary cell lines, oncogene-induced senescence has also been described in tumor cell lines (37,38).…”
Section: Discussionsupporting
confidence: 71%
“…These oncogenes are able to transform cells, but only in collaboration with other oncogenes such as MYC (31,32). Similar results have been described for ectopic expression of other components of the RAS pathway, such as RAC1 and RAF (33,34), as well as other oncogenes, including E2F and STAT5A (35,36). Although, in most studies, these experiments were conducted in primary fibroblasts or other primary cell lines, oncogene-induced senescence has also been described in tumor cell lines (37,38).…”
Section: Discussionsupporting
confidence: 71%
“…13,14 It is possible that one of the subunits is compensated because of the loss of other subunits. Therefore, we determined the mRNA and protein levels of NADPH oxidase major components such as p47 phox , gp91…”
Section: Up-regulation Of Nox4 In Lungs Of P47 Phoxϫ/ϫ and Gp91 Phoxϫmentioning
confidence: 99%
“…Recent studies have shown that NADPH oxidase subunits are under tight regulatory control in physiological conditions. 13,14 For example, a specific disruption of Rac1 in mouse embryonic fibroblasts leads to an increase in ROS level that is attributable to a compensatory increase in Rac3, another component of NADPH oxidase. 13 Furthermore, Rac1 was up-regulated in hematopoietic cells deficient in Rac2.…”
Section: Cigarette Smoke (Cs) Induces Recruitment Of Inflammatory Celmentioning
confidence: 99%
“…In this context, Rac1 regulates gene expression, cell cycle progression, cell spreading, rearrangement of the actin cytoskeleton, and activation of the nonphagocytic NADPH (22), while Rac2, besides controlling actin-mediated functions, is necessary for activation of phagocytic NADPH oxidase (3,18). The recent observation that fibroblasts lacking Rac1 upregulate Rac3 activation and cellular ROS suggests a potential role for this Rac family member in ROS synthesis (7). Mesangial cells express Rac1 (19,33), and this small GTPase is required for regulating angiotensin II-dependent ROS production (19), clearly suggesting that Rac1 can control ROS generation in this glomerular cell type.…”
mentioning
confidence: 99%